2019
DOI: 10.22452/mjcs.sp2019no3.9
|View full text |Cite
|
Sign up to set email alerts
|

Iot Security Risk Management Model for Healthcare Industry

Abstract: Internet of Things (IoT) is predicted as one of the biggest emerging environments in the future that creates simultaneous smart communication between machines or a variety of digital devices. Besides improving how data can be controlled, monitored and collected, IoT also allows us to generate revenue through the identifying of new business opportunities and deployment of advanced analytics processes for decision-making purposes. IoT enables us to accelerate changes in the healthcare environment in improving pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…This section presents a general overview of risk management approaches against cyber-attacks. This study identified 23 primary studies, of which two focused on mobile [153,154], six focused on IoT devices [107,[155][156][157][158]181], two focused on cyber-physical systems [168,169], four focused on either fog computing [111,160], the 5G edge-cloud ecosystem [167], or connected and autonomous vehicle (CAV) [159], and eight in general [61,93,[161][162][163][164][165][166]. Furthermore, four primary studies focused on APT [93,107,111,160], while the others are focused on either specific attacks such as DDOS attacks [181], DOS [167], SQL injections attacks [181], or privilege-induced attacks [154], or non-specific attacks [60,61,140,[155][156][157][158][159][161][162][163][164][165][166]…”
Section: Rq2: What Are the Proposed Defensive Mechanisms Available To...mentioning
confidence: 99%
See 4 more Smart Citations
“…This section presents a general overview of risk management approaches against cyber-attacks. This study identified 23 primary studies, of which two focused on mobile [153,154], six focused on IoT devices [107,[155][156][157][158]181], two focused on cyber-physical systems [168,169], four focused on either fog computing [111,160], the 5G edge-cloud ecosystem [167], or connected and autonomous vehicle (CAV) [159], and eight in general [61,93,[161][162][163][164][165][166]. Furthermore, four primary studies focused on APT [93,107,111,160], while the others are focused on either specific attacks such as DDOS attacks [181], DOS [167], SQL injections attacks [181], or privilege-induced attacks [154], or non-specific attacks [60,61,140,[155][156][157][158][159][161][162][163][164][165][166]…”
Section: Rq2: What Are the Proposed Defensive Mechanisms Available To...mentioning
confidence: 99%
“…As shown in Figure 9, the existing studies either proposed risk management approaches [93,[154][155][156]158,159,161,[165][166][167][168][169] or were integrated with other approaches such as access control [161,164], situational awareness [61], and game theory [107,111,160,162].…”
Section: Rq2: What Are the Proposed Defensive Mechanisms Available To...mentioning
confidence: 99%
See 3 more Smart Citations